2009
DOI: 10.1175/2009jpo4013.1
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Response of Surface Currents to the Wind in a Coastal Region

Abstract: Analysis of coastal surface currents measured off the coast of San Diego for two years suggests an anisotropic and asymmetric response to the wind, probably as a result of bottom/coastline boundary effects, including pressure gradients. In a linear regression, the statistically estimated anisotropic response explains approximately 20% more surface current variance than an isotropic wind-ocean response model. After steady wind forcing for three days, the isotropic surface current response veers 428 6 28 to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(96 citation statements)
references
References 59 publications
5
90
0
1
Order By: Relevance
“…This is in agreement with the results of Kirincich et al (2005) on the mid-shelf off central Oregon, Kim et al (2009) in waters of San Diego and Ardhuin et al (2009) on the western coast of France. In particular, Kim et al (2009) have reported anisotropic and asymmetric coastal surface current response to the wind in relation to the bottom and coastline boundary effects. The deflection angle also varies seasonally, being larger in summer than in winter.…”
Section: Air-sea Interaction Patterns and Timescalessupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the results of Kirincich et al (2005) on the mid-shelf off central Oregon, Kim et al (2009) in waters of San Diego and Ardhuin et al (2009) on the western coast of France. In particular, Kim et al (2009) have reported anisotropic and asymmetric coastal surface current response to the wind in relation to the bottom and coastline boundary effects. The deflection angle also varies seasonally, being larger in summer than in winter.…”
Section: Air-sea Interaction Patterns and Timescalessupporting
confidence: 92%
“…Yoshikawa et al (2007) identified a current profile corresponding to the Ekman spiral in the Tsushima Strait (based on observations from current profilers and HF radar) using EOF analysis. The wind impulse response and transfer functions have been widely discussed with HF radar currents in California and interpreted according to the Ekman theory by Kim et al (2009Kim et al ( , 2010. Zhao et al (2011) also attributed the subtidal flow to Ekman windinduced dynamics in waters of Qingdao (China).…”
Section: Air-sea Interaction Patterns and Timescalesmentioning
confidence: 99%
“…The correlation between the vertical shear in the alongshore currents and the alongshore windstress is dominated by currents in the surface-most ADCP bins (, 5 m). Recent calculations made from high-frequency radar-derived surface currents and local winds in the vicinity of the study site demonstrate that the local wind drives a surface current response that is a combination of direct forcing and geostrophically balanced pressure gradients due to upwelling-or downwelling-favorable winds (Kim et al 2009). It is possible that the lack of near-surface resolution in previous studies (Winant and Olson 1976;Lentz and Winant 1986) obscured the forcing relationship between the local winds and the surface currents.…”
Section: Discussionmentioning
confidence: 98%
“…잔차류의 동-서 성분 평균은 표층부터 저층까지 -0.07~-0.31 cm/sec (Bye, 1965;Churchill and Csanady, 1983;Wu, 1983;Weber, 1983;Kim, 2009 (Fig. 3), 만의 북부에서 유입된 담수는 표층을 통해 북쪽에서 남쪽으로 평균 5~15 cm/sec의 속도로 이동했다 (정 등, 2011a, 2011bJung et al, 2011;정 등, 2012b, 2012c.…”
Section: 조화분석 결과unclassified